Power relations among stakeholders in the implementation of national ICT policy: case of Malawi - Makoza, Frank (Department of Information Systems, 2017)
Purpose: Recent years have seen a growing number of low-income countries formulating and implementing national Information and Communication Technology (ICT) policies with the aim of supporting their socio-economic development agendas. For the majority of these countries, this exercise has been fraught with numerous challenges such as lack of resources; limited support for legal and regulatory frameworks; over-dependence on donors; lack of expertise; lack of implementation strategies; lack of policy championship; and limited participation of stakeholders. Consequently, the intended policy outcomes have not been adequately realised. To mitigate some of the challenges, there have been calls for promotion of more inclusive stakeholders participation in the formulation and implementation of national ICT policies. However, stakeholder participation may not be a silver-bullet to addressing policy implementation challenges since participation itself may be beset with power relations due to differences in beliefs, norms and values of the stakeholders themselves. The study analyses how power relations among stakeholders affect implementation of the national ICT policy. Using the case of Malawi, this study focuses on the implementation of national ICT policy in the context of a developing country. Research methodology: The study was premised in a critical research paradigm and used Critical Social Theory to analyse the interactions and practices of policy stakeholders in the execution of activities for the national ICT policy. The study analyses policy documents and interviews to highlight issues of domination, exclusion and assumptions in the national ICT policy implementation. Key findings: Power relations affected the recruitment and the implementation of the ICT policy. The government controlled the recruitment of stakeholders in the national ICT policy, however, other stakeholders demanded their inclusion in the policy implementation network. The recruitment process resulted in the membership in policy implementation network was elitist. The stakeholders had different interests in the policy and some performed multiple roles in policy implementation activities. The stakeholders mobilised and used different forms of resources to advance their interests in policy implementation activities. The differences in access to resources and capacity to mobilise these resources (legal, financial, information, human capacity) among the stakeholders led to power relations challenges. However, the exercise of power led to the circulation of power among the stakeholders and affected the policy implementation activities such as institutional settings, collaborations among stakeholders, coordination of policy and oversight of the policy. Power relations, to some extent, supported the dominant discourses that shaped the policy implementation to focus on demand perspective of ICTs, including ICT infrastructure initiatives, legal and regulatory frameworks. Value of the study: The study contributions are twofold: First, the study suggests theoretical propositions for explaining power relations among stakeholders in the implementation of national ICT policy; and second, the study makes recommendations for policymakers and actors in Malawi where there is urgent need to address socio-economic challenges and to improve the well-being of citizens using ICTs.